Reliability Analysis of Baremetal and FreeRTOS Applications on Microchip PolarFire SoC RISC-V Multiprocessors Using High-Energy Protons - Andre M. P. Mattos; Douglas A. Santos; Luigi Dilillo (IEEE Access)
Modern space applications are increasingly demanding reliable processing systems with high computational capabilities for missions with ambitious targets, tight budgets, and fast deployment. Hence, the space sector is accelerating the adoption of Commercial Off-The-Shelf (COTS) high-performance and reconfigurable processors. In this context, we propose the analysis and characterization of software applications’ reliability on a novel RISC-V-based processing system: Microchip’s PolarFire System-on-Chip (SoC). For that, we introduce reliability benchmarks using baremetal and FreeRTOS implementations and perform an experimental evaluation using high-energy protons, reporting Single-Event Effects (SEE) cross sections and the impact of Total Ionizing Dose (TID). Moreover, we discuss in detail the error propagation and masking, proposing a reliability metric to support the standardization of radiation effects reporting on complex processing systems. Finally, we evaluate the effectiveness of error mitigation and awareness in PolarFire SoC using built-in monitoring and test instrumentation with enhanced observability.